Right Axillary Mini-thoracotomy approach for surgical correction of Congenital Heart Disease - Bhattarai, A; Khakural, P; Pradhan, B (Journal of Institute of Medicine Nepal, 2024)
Introduction: We describe our initial experience with minimally invasive approach using Peripheral cardiopulmonary bypass (CPBP) and a 4-5 cm long right axillary mini-thoracotomy (RAMT) incision for surgical correction of congenital heart diseases. A right axillary mini-thoracotomy with the aid of peripheral CPBP is a surgical option that has been adopted in our institution in selected patients with congenital heart disease. We present our selection criteria, describe our technique, and analyze our results with this modified technique.Methods: This is retrospective descriptive study conducted at Green city Hospital, Kathmandu and the procedures were followed in accordance with the institutional guidelines for retrospective record review and protection of patient confidentiality. The preoperative variables, intraoperative data and postoperative outcomes of patients undergoing minimally invasive cardiac surgery were collected and analyzed.Results: Total 12 patients were included in the study who underwent a minimally invasive approach with the aid of peripheral CPBP for repairing congenital heart disease (CHD) in our institutions. Main diagnosis leading to surgery included: (1) ostium secundum atrial septal defect in 7 patients, (2) ostium secundum atrial septal defect with moderate tricuspid regurgitation in 3 patients, (3) perimembranous ventricular septal defect with patent ductus arteriosus in 1 patient, (4) ostium secundum atrial septal defect with core triatriatum in 1 patient. There were 6 females and 6 males. Median hospital stay was 4 days. There were no residual intracardiac anomalies at discharge two-dimensional echo, and all patients were satisfied with the surgical approach.Conclusion: The combination of RAMT and peripheral CPBP is safe and effective for treating some congenital heart disease with excellent clinical results.